2021
DOI: 10.3390/en14164766
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Exergy Analysis of Waste-Based District Heating Options through Case Studies

Abstract: The heating of the buildings, together with domestic hot water generation, is responsible for half of the total generated heating energy, which consumes half of the final energy demand. Meanwhile, district heating systems are a powerful option to meet this demand, with their significant potential and the experience accumulated over many years. The work described here deals with the conventional and advanced exergy performance assessments of the district heating system, using four different waste heat sources b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The rapid economic development has led to increasingly serious conflict between resources and the environment, which forced the world to search for sustainable and green energy to substitute traditional energy [1][2][3]. One promising and reliable opinion is to extract energy from the salinity difference between seawater and freshwater.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid economic development has led to increasingly serious conflict between resources and the environment, which forced the world to search for sustainable and green energy to substitute traditional energy [1][2][3]. One promising and reliable opinion is to extract energy from the salinity difference between seawater and freshwater.…”
Section: Introductionmentioning
confidence: 99%
“…In the last several years, advanced exergy analysis has been demonstrated in several applications. Ozcan et al [4] investigated a district heating system based on four types of waste heat sources: municipal solid waste cogeneration, thermal power, wastewater treatment, and cement production. The results obtained showed that the exergy destruction of the pump was mainly avoidable (endogenous), and it was mainly unavoidable for the heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Ozcan et al [2], advanced exergy analysis was used to investigate district heating (DH) systems connected to different waste heat sources. The authors demonstrated that by using advanced exergy analysis, additional information on avoidable, unavoidable, endogenous, and exogenous parts of exergy destruction in the components of the DH system could be obtained.…”
mentioning
confidence: 99%